Fracture load of colored and non-colored high translucent zirconia three-unit fixed dental prosthesis frameworks - Deyar Jallal Hadi Mahmood; Michael Braian; Abdul-Salam Khan; Armin Shabaz; Christel Larsson (Medical Journals Sweden, 2018)
Aim: The use of colored translucent zirconia may enable restorations of a more natural tooth-like appearance than previous opaque white zirconia. The shift from non-colored to colored zirconia may however entail a risk of reduced strength. The aim of the present study was to compare fracture load and fracture mode of fixed dental prostheses frameworks made of colored translucent zirconia to that of non-colored controls. Methods: A total of forty three-unit FDP frameworks were manufactured from two different high translucent zirconia materials (Zenostar, Wieland Dental, and DD cubeX2, Dental Direkt). Each group contained two subgroups, one colored and one non-colored. Coloring was performed before final sintering using two different infiltration techniques. All FDPs underwent an artificial aging process in the form of heat treatment, thermocycling and preloading whereafter the specimens were subjected to load until fracture. Fracture load and mode was registered. Results: For one of the zirconia materials, Zenostar, the non-colored frameworks showed significantly higher fracture loads (p < .0001) compared to its colored counterpart. No significant difference (p > .05) was found between colored and non-colored frameworks in the other zirconia material, DD cubeX2. All FDPs fractured through the connector. Some fractures ran through the mesial and some through the distal side of the connector but there were no significant differences in fracture mode between groups. Conclusion: Coloring before sintering of high-translucent zirconia may decrease the fracture load of FDP frameworks for certain materials and techniques. Fracture mode however, does not appear to be affected.